Depression among Patients with Schizophrenia in Ethiopian Mental Health Hospital: Association with Sociodemographic and Clinical Variables: A Cross-Sectional Study. (9th February 2021) - Tariku, Mandaras; Ali, Tilahun; Misgana, Tadesse; Hajure, Mohammedamin; Asfaw, Henock
Abstract : Background . Depression is a significant contributor to the global burden of disease and affects all individuals throughout their lifetime. Patients with schizophrenia are frequently attacked by depression during their total illness duration. Presence of comorbid depression in schizophrenia makes the patients more deteriorating and disabling course and poor outcome. Aim of the Study . To determine the prevalence of depression and highlight the associated sociodemographic and clinical factors in patients with schizophrenia in a specialized hospital in Addis Ababa, Ethiopia. Setting . This study was conducted at Amanuel Mental Specialized Hospital, Addis Ababa, Ethiopia. Methods . An institutional based cross-sectional study was conducted from May to June 2018. Depression was measured by Calgary Depression Scale for Schizophrenia on 455 samples of patient with schizophrenia and systematic sampling was used to select the study participants. Oslo Social Support Scale and Alcohol, Smoking, and Substance Involvement Screening Test were used to assess social support and substance use factors, respectively. A bivariable and multivariable logistic regression analysis model was performed to control the confounding factors. Odds ratio (OR) with the corresponding 95% confidence interval (95% CI) was determined to evaluate the strength of association. Results . A total of 445 patients responded to the questionnaire, which yields a response rate of 97.8%. The Magnitude of depression among schizophrenia patients was 24.9%. A multivariable logistic regression analysis model showed that being female [AOR 2.00, 95% CI: 1.25-3.18], divorced/widowed [AOR 2.39, 95% CI: 1.04-5.49], current substance use [AOR 1.95, 95% CI: 1.17-3.25], and poor social support [AOR 2.75, 95% CI: 1.35-5.61] were significantly associated with depression in schizophrenia. Conclusion . The magnitude of depression among schizophrenia was 24.9%. Being female, divorced/widowed, current substance use, and poor social support were associated with depression among patients with schizophrenia. Regular screening and prompt management of depressive symptoms among patients with schizophrenia is of particular importance to reduce the burden of the condition.